Kaempferol enhances intestinal repair and inhibits the hyperproliferation of aging intestinal stem cells in Drosophila - Zhao, Liusha; Luo, Ting; Zhang, Hong; Fan, Xinxin; Zhang, Qiaoqiao; Chen, Haiyang (Frontiers in Cell and Developmental Biology, 2024)
Intestinal stem cells (ISCs) are crucial for tissue repair and homeostasis because of their ability to self-renew and differentiate. However, as organisms age, ISC function diminishes, impairing tissue regeneration, weakening intestinal barrier integrity, and heightened disease susceptibility. Therefore, improving ISC function during injury and aging is vital for enhancing tissue repair and maintaining overall homeostasis in tissues and organs. Kaempferol, a flavonoid abundant in various fruits and vegetables, is well-regarded for its antioxidant, anti-inflammatory, and potential anticancer effects. Although its impacts on ISCs and the associated mechanisms remain inadequately understood. Drosophila, with its mammalian-like intestinal system and extensively studied ISC lineage, is recognized as an ideal model for ISC research. Our findings indicate that Kaempferol accelerates gut recovery after damage and improves the organism's stress tolerance. Moreover, Kaempferol suppresses the hyperproliferation of aging ISCs in Drosophila. Further investigation revealed that the regulatory effects of Kaempferol on ISCs are mediated through the reduction of endoplasmic reticulum (ER) stress in aging flies and the modulation of excessive reactive oxygen species (ROS) levels via ER-stress pathways. Furthermore, Kaempferol exerts regulatory effects on the insulin signaling pathway, thereby contributing to the attenuation of ISC senescence.